NIHSS Score Is Poorly Predictive of Proximal Occlusion in Acute Cerebral Ischemia - Maas, Matthew B. (2009)
BACKGROUND AND PURPOSE: Multimodal imaging is gaining an important role in acute stroke. The benefit of obtaining additional clinically relevant information must be weighed against the detriment of increased cost, delaying time to treatment and adverse events such a contrast-induced nephropathy. Use of NIHSS score to predict a proximal arterial occlusion (PO) is suggested by several case series as a viable method of selecting cases appropriate for multimodal imaging. METHODS: 699 patients enrolled in a prospective cohort study involving CTA imaging in acute stroke were dichotomized according to the presence of a PO, including a subgroup of 177 subjects with MCA M1 occlusion. RESULTS: The median NIHSS of patients found to have a PO was higher than the overall median (9 versus 5, p<0.0001). The median NIHSS score of patients with MCA M1 occlusion was 14. NIHSS score ≥ 10 had 81% positive predictive value for PO but only 48% sensitivity, with the majority of subjects with PO presenting with lower NIHSS scores. All patients with NIHSS ≥ 2 would need to undergo angiographic imaging to detect 90% of PO. CONCLUSIONS: High NIHSS score correlates with the presence of a proximal arterial occlusion in patients presenting with acute cerebral ischemia. No NIHSS score threshold can be applied to select a subgroup of patients for angiographic imaging without failing to capture the majority of cases with clinically important occlusive lesions. The finding of minimal clinical deficits should not deter urgent angiographic imaging in otherwise appropriate patients suspected of acute stroke.